Technology Tools for Leaders - Bearman, Andrea; Noyes, Jill (Open textbook library., 2023)
With the vast and varied technologies available to leaders, it is no doubt managing these technologies can be challenging. Yet, leaders must have a sense of which technologies will help the organization and its members to be successful. While an organizational leader does not need to be a technology expert, having an awareness of the impact technology has on an organization is important.